Empowering Farmers Through Assistance in Producing Alternative Photosynthetic Bacteria (PSB) Fertilizers for Corn Crops in Sigi District - Sinuhaji, Brenda; Wong, Gilbert; Serly, Putri; Setiawan, Risqi Firdaus; Virnanda, Putri (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2024)
Edufarmers Foundation is an institution under the auspices of PT. Japfa Comfeed Indonesia, Tbk., was established to accelerate farmers' productivity and develop the potential of Indonesian youth in agriculture. As part of this initiative, they have created a farmer field school program, where empowerment activities for farmers to increase agricultural productivity occur. One of the activities involves mentoring farmers in producing alternative photosynthetic bacteria fertilizers made from affordable materials to help increase crop productivity while reducing input costs. This activity aims to educate and assist farmers in reducing farming costs by utilizing alternative fertilizers made from materials available at home while still emphasizing the productivity of cultivated crops.